Role of transient receptor potential vanilloid subtype 2 in lower oesophageal sphincter in rat acid reflux oesophagitis - Kenjiro Matsumoto; Minako Suenaga; Yumi Mizutani; Kohei Matsui; Ayano Yoshida; Tomohiro Nakamoto; Shinichi Kato (Elsevier, 2021)
Gastroesophageal reflux disease (GERD) is a common gastrointestinal disorder. In the present study, we investigated TRP vanilloid subfamily member 2 (TRPV2) expression in lower oesophageal sphincter (LES) and its involvement in acid reflux oesophagitis in rats. Expression of TRPV2 and nerve growth factor mRNAs was significantly enhanced in LES of rats with reflux oesophagitis compared with normal rats. TRPV2 was mainly expressed in inhibitory motor neurons, and partly in intrinsic and extrinsic primary afferent neurons, and macrophages in LES of normal and reflux oesophagitis rats. Number of TRPV2-immunopositive nerve fibres was significantly increased, but that of nNOS-, CGRP-, and PGP9.5-nerve fibres was not changed in reflux oesophagitis compared with normal group. Probenecid produced nitric oxide production and relaxation in LES and this response was significantly enhanced in oesophagitis compared with normal group. Probenecid-induced relaxant effect was blocked by a TRPV2 inhibitor, tranilast, and a NOS inhibitor, NG-nitro-l-arginine methyl ester, in reflux oesophagitis rats. Oral administration of tranilast significantly improved body weight loss, oesophageal lesions, and epithelial thickness in oesophagitis model. These results suggest that up-regulation of TRPV2 in inhibitory motor neurons is involved in LES relaxation in oesophagitis model. TRPV2 inhibition might be beneficial for treatment of GERD.